2014
DOI: 10.1186/s13018-014-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Expansive open-door laminoplasty secured with titanium miniplates is a good surgical method for multiple-level cervical stenosis

Abstract: BackgroundLaminoplasty is an effective procedure for treating cervical spondylotic myelopathy (CSM). Little information is available regarding the surgical outcomes of expansive open-door laminoplasty (EOLP) when securing with titanium miniplates without bone grafting. This study is aimed to elucidate the efficacy of and problems associated with EOLP secured with titanium miniplates without bone grafting, thereby enhancing future surgical outcomes.MethodsThis is a retrospective study. The study participants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 44 publications
1
48
1
Order By: Relevance
“…Most of these studies used the JOA score as a parameter of clinical outcome. They reported that laminoplasty provided significant enhancement of the JOA score in the short-term, mid-term, and long-term follow-up [34][35][36][37][38][39]. However, Sakaura et al [40] reported that the average JOA score was at its highest point in 12 months of follow-up and decreased slightly to 14.9 in the final follow-up.…”
Section: Clinical Outcomementioning
confidence: 96%
See 2 more Smart Citations
“…Most of these studies used the JOA score as a parameter of clinical outcome. They reported that laminoplasty provided significant enhancement of the JOA score in the short-term, mid-term, and long-term follow-up [34][35][36][37][38][39]. However, Sakaura et al [40] reported that the average JOA score was at its highest point in 12 months of follow-up and decreased slightly to 14.9 in the final follow-up.…”
Section: Clinical Outcomementioning
confidence: 96%
“…Similarly, Heller et al [42] reported that both laminoplasty approaches exhibited similar good clinical outcomes. Furthermore, the recovery rate (RR) of laminoplasty was greater than 50% in the short-term, mid-term, and long-term follow-up [35,[38][39][40][41]. On the other hand, Uehara et al [34] reported that RR was 47.1% in the final follow-up, but 55.9% immediately after operation.…”
Section: Clinical Outcomementioning
confidence: 97%
See 1 more Smart Citation
“…The normal cervical aging process, congenital narrowing aggravated by acute trauma and bony malformations were identified as the primary causes of cervical stenosis that result in myelopathy. [1][2][3][4][5] Titanium miniplates fixation can be used to instantly reconstruct the spinal canal to restore its integrity. A relatively stable mechanical environment is conducive to bone slot healing on the door axial side and is also conducive to left and right muscle strength balance in the neck.…”
Section: Discussionmentioning
confidence: 99%
“…With these methods, decompression is achieved and the biomechanical integrity is maintained. [3][4][5] Since the design of classic open-door laminoplasty with the use of sutures, this procedure has modification to reduce complications, such as restenosis and axial symptoms.…”
Section: Introductionmentioning
confidence: 99%